Lattice shear and non-random rotation of Au nanoparticles under electron-beam irradiation. (December 2022) - Lee, Sung Bo; Kang, Sung-Gyu; Jung, Jinwook; Sung, Simoon; Yoo, Seung Jo; Han, Heung Nam
Abstract: Structural evolution of Au nanoparticles on amorphous carbon under electron-beam irradiation was examined at the atomic scale through in situ high-resolution transmission electron microscopy. Under electron-beam irradiation, some nanoparticles underwent lattice shear and fluctuation. The d-spacing and interplanar angle constantly and gradually changed, revealing metastable structures deviating from face-centered cubic Au. Rather than undergoing lattice fluctuation, some nanoparticles rotated. The nanoparticles did not rotate randomly, but followed a rule. As a nanoparticle rotated, one family of lattice planes constituting an initial zone axis remained parallel to the incident electron beam. Although the structural change and motion of nanoparticles under electron-beam irradiation have been examined in the literature, the aforementioned atomistic behavior has never been unveiled. We relate the phenomena to electron-beam-induced heating caused by inelastic collision between incident electrons and atomic electrons and momentum transfer during electron irradiation. Graphical abstract: Image, graphical abstract